Legal Considerations of Judges in Imposing Coaching Sanctions Against Children of Thieves with Objection - Vita Hestiningrum; Erna Dewi; Ahmad Irzal Fardiansyah (Pancasila and Law Review, 2020)
Criminal acts committed by children should be placed in LPKA as referred to in the law on juvenile justice, however the judge in this decision prefers to place the child in the development of a boarding school, of course in this case the judge has his own considerations. This paper will examine the basic legal considerations of judges in imposing criminal guidance on children who are criminal offenders of theft with weighting, the suitability of decision Number: 8/Pid.Sus-Anak/2016/PN.Kot with the demands of the Public Prosecutor, and the mechanism for implementing the verdict. Number: 8/Pid.Sus-Anak/2016/PN.Kot. The research method used in this research uses a normative approach, namely normative research which is carried out by examining the laws and basic theories. As for the results of the research, it was found that the basis for judges' legal considerations in making decisions against children, that in the trial the judge saw the two children who committed the crime not because of the crime factor but because the dominant factor of juvenile delinquency and also the two children could still be mentally corrected by giving opportunity for both children will certainly provide protection for their rights. The judge's decision was not in accordance with the prosecutor's demands where there were differences, namely: first, the judge did not agree with the method of imposing penalties that put children in LPKA; second, the judge's freedom to impose sanctions is also a factor in the incompatibility between the prosecutor's demands and the judge's decision; third, the impact of the harm caused by the two children was not too big. The mechanism for implementing the Decision Number:8/Pid.Sus-Anak/2016/Pn.Kot where the judge handed down the punishment of coaching in the institution to the two defendants in the form of an obligation to participate in a coaching program at the Islamic Boarding School, so that the guidance method followed the guidance method in the pesantren. Based on the results of the research conducted, it is recommended that the Public Prosecutor pay more attention to aspects of benefit in imposing criminal sanctions on children. In addition, the judge's future considerations should reflect justice and progressive steps.